Regional Logistics in Improving the Defense Economy in the Region - Arifin, Ahmad; Saputro, Guntur Eko; Haetami, Haetami (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
Covid-19 has had an impact not only on health but also on the resilience of the national economy. Learning from the history of war, if we have weapons without food reserves, it will be messy as well as increasing food security to anticipate the impact of disease outbreaks such as Covid-19 which could happen again in the future. The Ministry of Defense is serious about developing the Food Estate Program by reviewing several potential land locations for planting strategic commodities. The plan to develop the "Food Estate" area in Central Kalimantan launched by the President of the Republic of Indonesia Joko Widodo is a collaboration between the Ministry of Defense, the Ministry of PUPR, the Ministry of Agriculture, the Ministry of Environment and Forestry and the Ministry of SOEs. The research method uses descriptive qualitative. The results of the study show that the strength of food security is no less important than the strength of weapons, especially in dealing with the current situation such as the impact of the Covid-19 pandemic. For this reason, Indonesia must have adequate food reserves.